2019
DOI: 10.3390/biom9090477
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate-Based Macromolecular Crowding-Induced Stabilization of Proteins: Towards Understanding the Significance of the Size of the Crowder

Abstract: There are a large number of biomolecules that are accountable for the extremely crowded intracellular environment, which is totally different from the dilute solutions, i.e., the idealized conditions. Such crowded environment due to the presence of macromolecules of different sizes, shapes, and composition governs the level of crowding inside a cell. Thus, we investigated the effect of different sizes and shapes of crowders (ficoll 70, dextran 70, and dextran 40), which are polysaccharide in nature, on the the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 125 publications
(215 reference statements)
0
23
0
Order By: Relevance
“…The extent of stabilization of α-LA by the crowders (ficoll 70, dextran 70, and dextran 40) increases with the increasing concentration of the crowding agents due to the excluded volume effect and the small-sized and rod-shaped crowder, i.e., dextran 40, causing more pronounced stabilization of the protein in comparison with dextran 70 and ficoll 70 [ 118 ]. The structure of the protein in these experiments remains unperturbed.…”
Section: Unfolding Of α-Lactalbumin Caused By Heat and Various Denmentioning
confidence: 99%
“…The extent of stabilization of α-LA by the crowders (ficoll 70, dextran 70, and dextran 40) increases with the increasing concentration of the crowding agents due to the excluded volume effect and the small-sized and rod-shaped crowder, i.e., dextran 40, causing more pronounced stabilization of the protein in comparison with dextran 70 and ficoll 70 [ 118 ]. The structure of the protein in these experiments remains unperturbed.…”
Section: Unfolding Of α-Lactalbumin Caused By Heat and Various Denmentioning
confidence: 99%
“…While both computational [ 3 , 4 ] and experimental [ 1 ] approaches agree that crowding shifts thermodynamic equilibria of reactions towards products, the influence of crowding on reaction kinetics, especially those involving enzymes, is not as well understood. Crowding usually decreases the catalytic activity for diffusion-limited reactions due to impeded enzyme-substrate encounters [ [5] , [6] , [7] , [8] ]. For transition-state-limited reactions, though, crowding effects are less predictable due to the complex, often opposing, interplay of excluded volume, viscosity, soft interactions, and hydration effects [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…A depletion layer is only observed with crowders larger than the protein of interest and the thickness of this layer is directly correlated with the size of the crowder [ 47 ]. At the same time, the high concentration of crowder beyond the depletion layer lowers the activity of water [ 8 ], creating an osmotic force that dehydrates the protein surface [ 48 ]. Since unfolded proteins have a higher solvent accessible surface areas than the native state, the unfolded form experiences more dehydration, thereby stabilizing the folded protein [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Native cellular environments, such as the cytoplasm, are packed with biomacromolecules that subject proteins to highly confined and crowded environments, and these conditions have been shown to impact the equilibria of biochemical processes such as protein folding, as well as protein function and stability [ 2 , 3 ]. Given that traditional experimental protocols for the study of protein fates involved dilute buffer systems and did not replicate the in vivo conditions, new models have been developed to mimic natural confinement and crowding by using macromolecules, mesoporous silica matrices, reverse micelles, or hydrogels [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 25 ]. These studies demonstrated significant effects on several protein fates, including activity and functional stability, their interactions with self and other proteins, and unfolding and aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…Inside cells, proteins exist and function in highly crowded and compartmentalized environments that have a significant impact on several of their functions, including diffusion, enzymatic activity, protein–protein interactions, and folding, unfolding, and refolding [ 5 , 6 ]. Several studies have proposed the use of high concentrations of natural and synthetic macromolecules to study crowding [ 7 , 8 , 9 , 10 ], and encapsulating proteins within the pores of silica, polyacrylamide, or other hydrogels to study confinement [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. These studies have contributed to the mechanistic understanding of how proteins behave in vivo, as well as to unravel the differences between how confinement and crowding influence protein function [ 14 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%